Misinterpretations of syariah may lead to violence - Bakar, Osman (New Straits Times Press (M) Bhd., 2023)
Extremism is spreading like wildfire, as if it is a true reflection of human nature. Its threat to humanity is clear. If we want to secure a more peaceful social order, we need to address this social disease and identify its roots. Extremism is not the monopoly of religion. It could be the child of secular political ideologies. It could also be the product of religious political ideologies.